A CFD study of the effects of pipe bending angle on pressure piling in coal dust explosions in interconnected vessels. (March 2022) - Olugbemide, Damilare I.
Abstract: In industrial applications handling potentially explosive mixtures, bends with various bending angles are often incorporated into pipes to achieve a change of process flow direction. However, the effect of pipe bending angle on pressure piling—a major explosion hazard in interconnected vessels—has been sparsely studied for dust explosions. In this study, the effect of pipe bending angle on pressure piling in coal dust explosion in fully enclosed interconnected vessels was studied using computational fluid dynamics (CFD) modelling. The pipe bending angle was varied from 0° to 165°. The angle convention used in this study was such that 0° represents a straight pipe, while 165° represents the most "acute" angle used, with the pipe almost forming a U-tube at 165°. The experimental work of Lunn et al. (1996) was used to validate the simulation results. Three major effects of pipe bends on pressure piling are reported in this study: the effect on the instantaneous pressure spike; the effect on the rate of pressure rise; and the effect on the residual pressure in the interconnected system. Simulation results show that the highest severity of pressure spike and rate of pressure rise occurred in the straight pipe system, whereas the most severe case of residual pressure occurred in the curved pipe systems. As the bending angle increased, the residual pressure increased. The combination of two 45° bends used instead of a single 90° bend reduced the severity of pressure piling. These findings have practical implications for industrial applications, such as the choice of pipe bending angles and multiple bends.